Ideological resistance to veg*n advocacy: An identity-based motivational account - De Groeve, Ben; Bleys, Brent; Hudders, Liselot (Frontiers in Psychology, 2022)
Animal-based diets in Western countries are increasingly regarded as unsustainable because of their impact on human health, environmental and animal welfare. Promoting shifts toward more plant-based diets seems an effective way to avoid these harms in practice. Nevertheless, claims against the consumption of animal products contradict the ideology of the omnivorous majority known as carnism. Carnism supports animal-product consumption as a cherished social habit that is harmless and unavoidable and invalidates minorities with plant-based diets: vegetarians and vegans (veg*ns). In this theoretical review, we integrate socio-psychological and empirical literature to provide an identity-based motivational account of ideological resistance to veg*n advocacy. Advocates who argue against the consumption of animal products often make claims that it is harmful, and avoidable by making dietary changes toward veg*n diets. In response, omnivores are likely to experience a simultaneous threat to their moral identity and their identity as consumer of animal products, which may arouse motivations to rationalize animal-product consumption and to obscure harms. If omnivores engage in such motivated reasoning and motivated ignorance, this may also inform negative stereotyping and stigmatization of veg*n advocates. These “pro-carnist” and “counter-veg*n” defenses can be linked with various personal and social motivations to eat animal products (e.g., meat attachment, gender, speciesism) and reinforce commitment to and ambivalence about eating animal products. This does not mean, however, that veg*n advocates cannot exert any influence. An apparent resistance may mask indirect and private acceptance of advocates’ claims, priming commitment to change behavior toward veg*n diets often at a later point in time. Based on our theoretical account, we provide directions for future research.